Training of literacy-oriented teaching material development in MTs Al Ikhlas Soe, East Nusa Tenggara - Nurdiyah Lestari (Universitas Muhammadiyah Malang, 2020)
In accordance with the paradigm of 21st century education, teachers are required to facilitate students with the learning process which addresses the improvement of students’ higher thinking skill. The community service which was conducted in MTs Al Ikhlas Soe, East Nusa Tenggara was aimed at: 1) culturing as well as developing students’ literacy in school; 2) improving students’ capacity in literacy; 3) managing students’ knowledge and higher thinking skill, as considerable as 4) elevating teachers’ professionalism so that learning process can be more effective and efficient. The methods used were lecture, discussion, brainstorming, simulation, and assignment. The materials delivered were about the arrangement and development of literacy-oriented teaching materials. The product produced from the training was implemented in learning process on VII graders. This was aimed to observe whether there was an improvement gained after the training given. The participants of this community service were 13 teachers and 34 students of MTs Al Ikhlas Soe. The results showed that teachers’ skill in arranging teaching materials has been improved. Furthermore, students’ understanding of the concept or their knowledge related to the materials has been upgraded after experiencing the implementation of literacy-oriented learning.